Refugees and Foreign Direct Investment: Quasi-Experimental Evidence from U.S. Resettlements - Anna Maria Mayda; Christopher Parsons; Han Pham; Pierre-Louis Vézina (Institute of Labor Economics (IZA), 2019)
We exploit the designs of two separate U.S. refugee dispersal policies to provide causal evidence that refugees foster outward FDI to their countries of origin. Drawing upon aggregated individual-level refugee and project-level FDI data, we first leverage the quasi-random distribution of refugees "without U.S. ties" after the enactment of the 1980 Refugee Act, to show that outward FDI to refugees' countries of origin grew more from those U.S. commuting zones that hosted greater numbers of refugees after 1990. Secondly, we exploit the specificities of the Indochina Migration and Refugee Assistance Act, which resulted in a quasi-experimental dispersal of Vietnamese refugees in 1975, to provide causal evidence that Vietnamese refugees fostered FDI to their home region, while national domestic reforms in Vietnam amplified the positive FDI-creating effects of the overseas Vietnamese diaspora. Overall, our results highlight a new mechanism through which refugees foster development to their origin countries.
Keywords: F21; F22; F23; 330; refugees; networks; foreign direct investment